Low BALF CD4 T cells count is associated with extubation failure and mortality in critically ill covid-19 pneumonia. (31st December 2022) - Singh, Gurmeet; Martin Rumende, Cleopas; Sharma, Surendra K.; Rengganis, Iris; Amin, Zulkifli; Loho, Tonny; Hermiyanti, Emmy; Harimurti, Kuntjoro; Wibowo, Heri
Abstract: Background: Critically ill COVID-19 pneumonia is one of the main causes of extubation failure and mortality. Understanding clinical characteristics, laboratory profiles and bronchoalveolar lavage fluid (BALF) immunopathology may help improve outcomes in critically ill COVID-19 pneumonia. We aimed to describe clinical characteristics, laboratory profiles and BALF immunopathology based on lung severity in critically ill COVID-19 pneumonia patients. Materials and methods: Forty critically ill severe pneumonia patients requiring invasive mechanical ventilation in Cipto Mangunkusumo General (National Tertiary Referral Hospital), Indonesia within November 2020–January 2021 were enrolled in this study. Early BALF collection was performed after patients' intubation. Clinical characteristics, laboratory profiles and BALF biomarkers (sTREM-1, alveolar macrophage amount and function, IL-6, IL-17, CD4 T-cells, Tregs, SP-A and Caspase-3) were observed and analysed. Outcomes were measured based on extubation failure (within 19 days) and 28-days mortality. Univariate and bivariate analyses were performed. Results: Early bronchoscopy was performed in an average of 4 h (SD = 0.82) after patients' intubation. Twenty-three and twenty-two patients had extubation failure (within 19 days) and 28-days mortality, respectively. In the baseline clinical characteristics of critically ill COVID-19 patients, we found no significant differences in the extubation and mortality status groups. In the laboratory profiles of critically ill COVID-19 patients, we found no significant differences in the extubation status groups. In critically ill COVID-19 pneumonia patients, there was a significant high D-dimer levels in survived group ( p  = .027), a significant low BALF CD4 T-cells count in the right lung ( p  = .001) and a significant low BALF CD4 T-cells count ( p  = .010 and p  = .018) in severely affected lung with extubation failure and mortality. Conclusions: BALF CD4 T-cells count evaluation of severely affected lung is associated with early extubation failure and mortality in critically ill COVID-19 pneumonia patients. KEY MESSAGE: Few studies have been conducted during the peak COVID-19 period analysing combined bronchoalveolar lavage fluid (BALF) immunopathology biomarkers within four hours of intubation to assess extubation failure and mortality. In this study, we reported eight BALF immunopathology biomarkers (sTREM-1, alveolar macrophage, IL-6, IL-17, CD4 T-cells, Tregs, SP-A and Caspase-3). We found significantly low BALF CD4 T-cells count in the right lung, and low BALF CD4 T-cells count in severely affected lung of critically ill COVID-19 pneumonia patients in extubation failure and mortality.